Pengaruh Tablet Effervescent Daun Adas (Foeniculum Vulgare Mill) untuk Meningkatan Produksi ASI pada Ibu Menyusui - Sa’adah, Laila Chomsatus; Wijayanti, Krisdiana; Marsum, Marsum (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Breast milk is a natural nutritional intake and the process of exclusive breastfeeding has obstacles experienced by mothers that cause failure in breastfeeding their babies. Factors that cause such as the mother's perception that breast milk production is lacking, therefore efforts are needed to increase breast milk production. Non-pharmacological therapy by consuming fennel leaf effervescent tablets that are rich in saponins as an alternative to increase breast milk production. The general objective of this study was to determine the effectiveness of fennel leaf effervescent tablets on breast milk production in postpartum breastfeeding mothers with baby weight indicators. This study used a type of quasy experiment research using a pre-post test design with control group. The number of samples in this study were 30 respondents. Each group was given an intervention for 14 days in the intervention group, namely the administration of fennel leaf effervescent tablets and the control group by giving placebo effervescent tablets. Data analysis using Repeated Measure Anova and Independent Sample T test. The results of the baby's weight were significant differences between day 14, day 21, day 28 in the intervention group and control group with a value of p = 0.000. From the results of the study, the administration of fennel leaf effervescent tablets can increase breast milk production in breastfeeding mothers with baby weight indicators. Keywords: Effervescent Tablets, Fennel Leaf, Breast Milk Production.  ABSTRAK Air Susu Ibu (ASI) suatu asupan gizi alami dan proses pemberian ASI eksklusif terdapat kendala yang dialami ibu yang menjadi penyebab kegagalan dalam pemberian ASI kepada bayinya. Faktor yang menyebabkan yaitu seperti presepsi ibu bahwa produksi ASI kurang, maka dari itu diperlukan upaya untuk meningkatkan produksi ASI. Terapi non farmakologi dengan mengkonsumsi tablet effervescent daun adas yang kaya akan saponin sebagai alternatif untuk meningkatkan produksi ASI. Tujuan umum dari penelitian ini adalah mengetahui efektifitas tablet effervescent daun adas terhadap produksi ASI pada ibu nifas menyusui dengan indikator berat badan bayi. Penelitian ini menggunakan jenis penelitian quasy experiment dengan menggunakan rancangan pre-post test design with control group. Jumlah sampel dalam penelitian ini adalah 30 responden. Setiap kelompok diberikan intervensi selama 14 hari pada kelompok intervensi yaitu pemberian tablet effervescent daun adas dan kelompok kontrol dengan pemberian tablet effervescent placebo. Analisis data menggunakan Repeated Measure Anova dan Independen Sample T test. Hasil berat badan bayi terdapat perbedaan signifikan antara hari ke 14, hari 21, hari 28 pada kelompok intervensi dan kelompok kontrol dengan nilai p=0,000. Dari hasil penelitian pemberian tablet effervescent daun adas dapat meningkatkan produksi ASI pada ibu menyusui dengan indikator berat badan bayi. Kata Kunci: Tablet Effervescent, Daun Adas, Produksi ASI.